Measuring Academic Jealousy among Faculty Members: Scale Development, Psychometric Validation, and Network Analysis - Khasawneh, Yusra Jadallah Abed; Gharaibeh, Mahmoud; Al-Rousan, Ayoub Hamdan; Ayasrah, Mohammad Nayef; Khasawneh, Mohamad Ahmad Saleem; Ayasrah, Asma Nayef (Psychiatric quarterly, 2025)
This study aimed to develop, evaluate the psychometric properties, and explore the Academic Jealousy among Faculty Members Scale (AJFM) network structure. This scale was developed as a new scale to assess jealousy-related experiences among Arab university faculty. A two-phase, cross-sectional design was conducted in Jordan. In phase one, items were generated through literature review, an expert committee, and pilot testing. Accordingly, a 32-item pool was developed and refined to 24 items via face and content validity procedures. In phase two, construct validity was assessed using exploratory factor analysis (EFA) with promax rotation (n = 288), followed by confirmatory factor analysis (CFA), gender invariance testing (configural, metric, scalar, strict), reliability analysis (Cronbach's α, test-retest ICC), and network analysis (EBICglasso, centrality indices). EFA supported a three-factor structure-Career Progression Jealousy, Collegial Recognition Jealousy, and Research Achievement Jealousy-explaining 39.6% of variance. CFA confirmed acceptable model fit, and gender invariance was supported across all levels (ΔCFI ≤ 0.01; ΔRMSEA ≤ 0.015). Reliability was strong (α = 0.808-0.853), with excellent test-retest consistency (ICC = 0.822). Network analysis highlighted central nodes (e.g., tenure-related anxiety, evaluation-based envy) with high centrality, suggesting their psychological salience in faculty dynamics. The AJFM scale provides a psychometrically robust, culturally relevant instrument to assess jealousy among academics. It may help identify patterns of emotional strain potentially linked to professional stress and mental health challenges in competitive academic settings.